"Leave the Fads to the Yankees": The Campaigns for Commission and City Manager Government in Toronto, 1910-1926 - Petersen, Patricia (Urban History Review / Revue d'histoire urbaine, 1991)
Does the border between the United States and Canada make a difference? To a political scientist it does for the obvious reason: the border defines two different political entities with different forms of government, different political customs and conventions. Two attempts in the first thirty years of the twentieth century to change the structure of the government of the City of Toronto illustrate the difference the border can make.The two proposals, commission government and city manager government, had originated with municipal reformers in the United States during the Progressive Era. The main idea behind both plans was to concentrate the executive and legislative authority in one governing unit. Commission and city manager government, however, attracted only a few supporters in the City despite their extreme popularity in the United States. City government in Toronto was not considered as bad as the government in those cities in the United States that had changed to new forms. Moreover, the proposals were American innovations and Toronto politicians were wary of American fads, especially ones like these which were drawn "from the uncertain spheres of political theory."